From domestic women to sensitive young men translating the individual in early colonial Korea - Yang, Yoon Sun (Cambridge, Massachusetts The Harvard University Asia Center, 2017)
Examines how the European notion of the individual put down its roots in Korean literature, especially through literary figures, in the early twentieth century. Using Korean literary examples, it calls into question the belief that there is only one kind of individuality transferable across cultural, temporal, and gender boundaries."--Provided by publisher.
Enlightened daughter, benighted mother -- From female ghosts to ghostly womanhood -- Unbound desire: femme fatales in the fin de siecle scene -- Sapphic marriage and radical domesticity -- Sensitive young men and the private desire for progress.
Includes bibliographical references (pages 189-202) and index.
Keywords: Korean literature -- 20th century -- History and criticism; Korean literature -- Western influences; Individuality in literature; Identity (Psychology) in literature